PANDANGAN ORANG MUDA KATOLIK TERHADAP FENOMENA FRIENDS WITH BENEFITS RELATIONSHIP - Erni Dameria Simare Mare; Agustinus Tri Edy Warsono (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2023)
The phenomenon of Friends with Benefits Relationship is a phenomenon that is commonly known among young Catholics. The phenomenon of Friends with Benefits Relationships (hereinafter abbreviated as: FwBRs) originates in western culture which is then adopted by the Indonesian youth. FwBRs becomes a new term in in regard to premarital sex or casual sex. The perception and experience of the Catholic youth towards the FwBRs phenomenon will influence the condition of youth morality in terms of the future of the Church. The purpose of this study is to identify the Catholic youth’s perception on premarital sex or FwBRs. The method applied in this study is qualitative research method with phenomenological approach. The data collection technique applied is in-depth interviews with informants who had been or are currently performing FwBRs relationship. The analysis technique applied is Interpretative Phenomenological Analysis (IPA). The results of the research are presented systematically according to the experiences of the informants. The literature study on Church documents was carried out by the researchers in regard to describe the Church's way of responding the FwBRs phenomenon. From the results of the research, it is concluded that the phenomenon of FwBRs is commonly known among the young Catholics and that the young people is aware of the consequence of being involved in this phenomenon is that it may bodily injure and that it may obscure the meaning of sex in a Catholic marriage.